Music cures music - Blackstone, Victoria (British Homeopathic Journal, 1993)
Each of us is a piece of music playing all the time. When that music is phased with a similar piece of music, healing is produced. Music cures music and silence is restored. Silence being produced equals cure. Every homoeopathic medicine is a piece of music with tune, pace and rhythm. If we can correctly identify the music of the patient, and the music of the medicine, we will go towards cure. The tune is the similimum, and the pace and rhythm are the potency and the repetition. The theme of this seminar is music.
Keywords: Mercurius solubilis; Manganum; Alumina; Kalium arsenicosum; Drosera; Sepia; Lac caninum; Lyssin